Freudian psychoanalysis in the work of Arthur Schnitzler Eyes Wide Shut - Janowska, Aleksandra (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Interpreting dreams was an important aspect of Sigmund Freud’s life. In his statements and works, he repeated multiple times that a dream is the fulfilment of a wish. Dream analysis had a huge impact on his subsequent research, including psychoanalysis and the theory of the subconscious. Through his work he contributed to people starting to analyze their dreams, and they continue to do so to this day. However, the difficulty in analyzing the dreams was their transience and length. This meant that remembering them was often problematic. Freudian psychoanalysis and the interpretation of dreams were frequent motifs in Artur Schnitzler’s work. One of them is Traumnovelle, or Eyes Wide Shut. The aim of the article is to show how Freudian psychoanalysis is presented in the work of the Austrian writer and why the symbolism of dreams and its meaning are so important in the context of the discussed work.